SENSITIVITY OF COMPUTED TOMOGRAPHY AS A DIAGNOSTIC TOOL IN DIFFERENTIATING NECK MASSES INTO BENIGN AND MALIGNANT LESIONS - VANDANA, MRUDULA; SRIRAMANENI, VENKATESWAR RAO; Valapala, Venkat Narayana Goutham (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: Neck masses have a diverse clinical profile that necessitates multimodality evaluation. Hence, the present study aids the use of computed tomography (CT) in identifying various structures in the neck, which are split into multiple regions by the cervical fascia. Methods: This multi-centric study was conducted at two tertiary care centers. Sixty patients were studied who were referred to the radiodiagnosis department for evaluation. In the present study, CT findings were correlated with pathological findings. Results: The results revealed that the sensitivity of CT in diagnosing and differentiating the neck mass was 86.3% and a positive predictive value of 100%, with a negative predictive value of 95.1%. Cross-sectional imaging of the CT of the neck provides detailed three-dimensional visualization of the masses and their relationship with adjacent blood vessels, glands, fascia, muscles, and neck spaces. The posterior extension of the lesion is better assessed by CT and surpasses ultrasonography. Conclusion: Bony involvement, either by a primary bony lesion or a direct invasion by the neck mass, can be better evaluated because of the differential attenuation values in CT.